Conflict Management in Organizations at Sariputra Indonesia University, Tomohon - Sjerly Maria Lumi; JAM Rawis; Shelty DM Sumual; Mozes M. Wulur (Peneliti.net, 2020)
Purpose of this study is to obtain empirical data about conflict management in organizations at Sariputra Indonesia University, Tomohon. The perspective of this research is descriptive qualitative with a phenomenological design. Data were collected through interviews, observation and documentation. Samples were taken using purposive sampling by means of snowball sampling. While the data analysis uses theanalysis technique Grounded Theory developed by Strauss and Corbin (1990: 57) went through procedures, namely open coding(Open Coding),centralized coding (Axial Coding),and selected coding (Selective Coding). The results of this study are: 1) Sources of conflict as the background of conflict are very important in the conflict planning process, 2) Foundation support plays an important role in planning and climate and culture. 3) Management of conflict by determining the conflict management approach brings positive and functional changes. 4) The success of the conflict management approach with conflict resolution, conflict stimulation, reducing conflict are the keys to the success of a higher education institution by creating a joint commitment in increasing organizational productivity.